Carbon-Hydrogen Bond Activation of Phenyldi(2- Thienyl)Phosphine at A Triruthenium Cluster Center (Journal of the Bangladesh Chemical Society, 2012)
Ketyl-initiated reaction between Ru3(CO)12 and phenyldi(2-thienyl)phosphine (PhPTh2) furnished simple phosphine-substituted triruthenium clusters [Ru3(CO)10(PhPTh2)21 and [Ru3(CO)9(PhPTh2)3] 2. Heating 1 in boiling benzene afforded [Ru3(CO)8{?3- PhThP(C4H2S)}(PhPTh2)] 3 by carbon-hydrogen bond cleavage of a coordinated thienylphosphine ligand. All three new clusters have been characterized by elemental analysis, IR and NMR spectroscopic data.DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11764 Journal of Bangladesh Chemical Society, Vol. 25(1), 1-6, 2012